2013
DOI: 10.1007/s00122-012-2029-x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and identification of a novel Ligon lintless-like mutant (Lix) similar to the Ligon lintless (Li1) in allotetraploid cotton

Abstract: Mutants are a powerful resource for studying gene structure, function, and evolution. In this present study, a novel Ligon lintless-like mutant (Lix), that has short fibers and deformed leaves and stems, was isolated from the progeny of transgenic cottons. The Lix mutant is similar in morphology to the Ligon lintless (Li1) mutant. Genetic analysis and molecular mapping were performed for the Lix and Li1 mutants. These two mutants are monogenic dominant mutants with distorted growth of vegetative and reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Recently, Gore et al [46] observed the same phenomenon when using RILs derived from a cross between TM-1 and NM24016. In our previous research to fine map the Ligon-lintless 1 ( Li 1 ) gene, we revealed a similar phenomenon [51], and so did Cai et al [52]. Chr.15 had a very big gap (80.47 cM) at the end of its long arm.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, Gore et al [46] observed the same phenomenon when using RILs derived from a cross between TM-1 and NM24016. In our previous research to fine map the Ligon-lintless 1 ( Li 1 ) gene, we revealed a similar phenomenon [51], and so did Cai et al [52]. Chr.15 had a very big gap (80.47 cM) at the end of its long arm.…”
Section: Discussionsupporting
confidence: 65%
“…This result may also imply that the genomic region harboring Li 1 locus is highly monomorphic. Recently, Cai et al [20] reported a similar phenomenon when mapping the Lix locus. One of their flanking markers, NAU3469, was 24.5 cM away from the Lix locus.…”
Section: Discussionmentioning
confidence: 67%
“…Mutant lines exhibiting very short seed fibers include the Ligon Lintless-1 and −2 lines ( Li 1 and Li 2 ) [18,19]. Recently, Cai et al [20] analyzed a man-made mutant Lix that showed similar phenotype to Li 1 . The understanding that initiation, elongation, and secondary cell wall synthesis are distinct developmental processes often leads to the utilization of the applicable mutant to study the specific process of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fiber mutants can be divided into three categories: fiberless seeds (such as Fbl and Sma-4(ha)), seeds with very shortlint fiber (such as Li1, Li2, and Lix) (Cai et al 2013;Karaca et al 2002;Kohel et al 1992), and fuzzless seeds with lint fiber (such as N1, sma-4 (fz), n2, xu142, and more than 100 recently reported naked mutants) (Rong et al 2005;Sun et al 2012;Turley and Kloth 2002). Because a single gene mutation in some of these mutants can affect the initiation and development of cotton fibers (Rong et al 2005;Sun et al 2012;Kohel et al 2002;Turley and Kloth 2008;Turley et al 2007), the isolation of these genes is critical to elucidate the molecular basis of cotton fiber development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a mutant with a similar phenotype controlled by a dominant gene was created and mapped to a region of chromosome (Chr.) 04(A), which was thought to be homoeologous to the region of Li1 on Chr.22(D) (Cai et al 2013). Because the Li1 mutant is a model for studying fiber elongation and both primary and secondary cell wall thickening processes, several groups have comprehensively explored gene alterations in the Li1 mutant.…”
Section: Introductionmentioning
confidence: 99%